Shorter intervals at peak SV vs.VO2max may yield high SV with less physiological stress - Colakoglu, M.; Ozkaya, O.; Aybars Balci, G.; Yapicioglu, B. (European Journal of Sport Science, 2015)
The purpose of this study was to evaluate whether greater and sustainable stroke volume (SV) responses may be obtained by exercise intensities corresponding to peak SV (SVpeak) vs. maximal O2 consumption (VO2max), and short vs. long intervals (SI vs. LI). Nine moderate- to well-trained male athletes competing at regional level specialists of cyclist, track and field volunteered to take part in the study (VO2max: 59.7 +/- 7.4 mL/ min/1kg.1). Follow familiarisation session, VO2max was determined, and then SVpeak was evaluated using exercise intensities at 40%.100% of VO2max by nitrous-oxide rebreathing (N2ORB) method. Then each separate participant exercised wattages corresponding to individual VO2max and SVpeak during both SI (SIVO2max and SISVpeak) and LI (LIVO2max and LISVpeak) workouts on a cycle ergometer. Main results showed that both SIVO2max and SISVpeak yielded greater SV responses than LIVO2max and LISVpeak (p /= 0.05). Mean SV responses were greater in LIsvpeak than in LIVO2max (p /=. 0.05), but there was no statistical difference between SIsvpeak and SIVO2max. However, there was significantly less physiological stress based on VO2, respiratory exchange ratio, heart rate and rate of perceived exhaustion in SVpeak than in VO2max intensities ( p /= . 0.05). Moreover, SV responses at exercise phases increased in the early stages and remain stable until the end of LIVO2max and SISVpeak workouts ( p > 0.05), while they were gradually decreasing in LIVO2max and LISVpeak sessions ( p /= . 0.05). In conclusion, if the aim of a training session is to improve SVpeak with less physiological stress, SISVpeak seems a better alternative than other modalities tested in the present study.